Flagellar Perturbations Activate Adhesion through Two Distinct Pathways in Caulobacter crescentus - Hershey, David M.; Fiebig, Aretha; Crosson, Sean (mBio, 2021)
Understanding how bacteria colonize solid surfaces is of significant clinical, industrial and ecological importance. In this study, we identified genes that are required for Caulobacter crescentus to activate surface attachment in response to signals from a macromolecular machine called the flagellum. Bacteria carry out sophisticated developmental programs to colonize exogenous surfaces. The rotary flagellum, a dynamic machine that drives motility, is a key regulator of surface colonization. The specific signals recognized by flagella and the pathways by which those signals are transduced to coordinate adhesion remain subjects of debate. Mutations that disrupt flagellar assembly in the dimorphic bacterium Caulobacter crescentus stimulate the production of a polysaccharide adhesin called the holdfast. Using a genomewide phenotyping approach, we compared surface adhesion profiles in wild-type and flagellar mutant backgrounds of C. crescentus . We identified a diverse set of flagellar mutations that enhance adhesion by inducing a hyperholdfast phenotype and discovered a second set of mutations that suppress this phenotype. Epistasis analysis of the flagellar signaling suppressor ( fss ) mutations demonstrated that the flagellum stimulates holdfast production via two genetically distinct pathways. The developmental regulator PleD contributes to holdfast induction in mutants disrupted at both early and late stages of flagellar assembly. Mutants disrupted at late stages of flagellar assembly, which assemble an intact rotor complex, induce holdfast production through an additional process that requires the MotAB stator and its associated diguanylate cyclase, DgcB. We have assigned a subset of the fss genes to either the stator- or pleD -dependent networks and characterized two previously unidentified motility genes that regulate holdfast production via the stator complex. We propose a model through which the flagellum integrates mechanical stimuli into the C. crescentus developmental program to coordinate adhesion. IMPORTANCE Understanding how bacteria colonize solid surfaces is of significant clinical, industrial and ecological importance. In this study, we identified genes that are required for Caulobacter crescentus to activate surface attachment in response to signals from a macromolecular machine called the flagellum. Genes involved in transmitting information from the flagellum can be grouped into separate pathways, those that control the C. crescentus morphogenic program and those that are required for flagellar motility. Our results support a model in which a developmental and a mechanical signaling pathway operate in parallel downstream of the flagellum and converge to regulate adhesion. We conclude that the flagellum serves as a signaling hub by integrating internal and external cues to coordinate surface colonization and emphasize the role of signal integration in linking complex sets of environmental stimuli to individual behaviors.